Isolation, Characterization, and Transplantation of Cardiac Endothelial Cells. (27th October 2013) - Pratumvinit, Busadee; Reesukumal, Kanit; Janebodin, Kajohnkiart; Ieronimakis, Nicholas; Reyes, Morayma
Abstract : Isolation and ex vivo expansion of cardiac endothelial cells have been a recurrent challenge due to difficulties in isolation, cell heterogeneity, lack of specific markers to identify myocardial endothelial cells, and inadequate conditions to maintain long-term cultures. Herein, we developed a method for isolation, characterization, and expansion of cardiac endothelial cells applicable to study endothelial cell biology and clinical applications such as neoangiogenesis. First, we dissociated the cells from murine heart by mechanical disaggregation and enzymatic digestion. Then, we used flow cytometry coupled with specific markers to isolate endothelial cells from murine hearts. CD45+ cells were gated out to eliminate the hematopoietic cells. CD31+/Sca-1+ cells were isolated as endothelial cells. Cells isolated from atrium grew faster than those from ventricle. Cardiac endothelial cells maintain endothelial cell function such as vascular tube formation and acetylated-LDL uptake in vitro . Finally, cardiac endothelial cells formed microvessels in dorsal matrigel plug and engrafted in cardiac microvessels following intravenous and intra-arterial injections. In conclusion, our multicolor flow cytometry method is an effective method to analyze and purify endothelial cells from murine heart, which in turn can be ex vivo expanded to study the biology of endothelial cells or for clinical applications such as therapeutic angiogenesis.